2003
DOI: 10.1073/pnas.1733772100
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of type 5 adenylyl cyclase gene preserves cardiac function against pressure overload

Abstract: The sympathetic nervous system is designed to respond to stress. Adenylyl cyclase (AC) is the keystone of sympathetic transmission, yet its role in response to acute overload in the heart or in the pathogenesis of heart failure is controversial. We examined the effects of pressure overload, induced by thoracic aortic banding, in mice in which type 5 AC, a major cardiac AC isoform, was disrupted (AC5 ؊/؊ ). Left ventricular weight͞tibial length ratio (LVW͞TL) was not different between the WT and AC5 ؊/؊ at base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
164
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 185 publications
(177 citation statements)
references
References 34 publications
6
164
1
Order By: Relevance
“…Adenylyl cyclase (AC) has 9 major mammalian isoforms, of which type 5 plays a major role in regulation of the heart and brain, as well as other organs. We have found that disruption of type 5 AC (AC5 KO) in the mouse prolongs lifespan and protects against stress, [23][24][25] similar to what has been described in the other genetic models of longevity described earlier. It is our concept that the inhibition of AC5 could become a novel therapy for heart failure and here we elaborate the basis for this concept, reviewing the data resulting in longevity and stress resistance in the AC5 KO mouse.…”
supporting
confidence: 64%
“…Adenylyl cyclase (AC) has 9 major mammalian isoforms, of which type 5 plays a major role in regulation of the heart and brain, as well as other organs. We have found that disruption of type 5 AC (AC5 KO) in the mouse prolongs lifespan and protects against stress, [23][24][25] similar to what has been described in the other genetic models of longevity described earlier. It is our concept that the inhibition of AC5 could become a novel therapy for heart failure and here we elaborate the basis for this concept, reviewing the data resulting in longevity and stress resistance in the AC5 KO mouse.…”
supporting
confidence: 64%
“…AC1 knockout mice show impaired cerebellar long term potentiation and impaired development of the somatosensory cortex (17,18); AC3 knockout mice exhibit anosmia (19); AC5 knockout mice show reduced sensitivity to development of heart failure (20); and AC8 knockout mice exhibit altered stress-induced anxiety responses (21). Collectively, the differential regulation, tissue distribution, and function of AC isoforms indicate that isoform-specific AC inhibitors could constitute promising drugs.…”
mentioning
confidence: 99%
“…Therefore, the demonstration of improved exercise performance in the AC5 KO model is particularly germane, as this is also a model for longevity (Yan et al ., 2007), and protects against cardiovascular stress (Okumura et al ., 2003; Lai et al ., 2013), diabetes, and obesity (Ho et al ., 2015). In view of the important link between exercise and longevity, it is surprising that of 20 mouse models we reviewed, only two studied exercise and found it to be increased.…”
Section: Discussionmentioning
confidence: 99%